Evaluating the use of the autodiametric method for estimating fecundity of Reinhardtius hippoglossoides, a species with an unusual oocyte development strategy. (29th August 2017) - Dominguez-Petit, R; Rideout, R M; Garabana, D; Lambert, Y; Hermida, M; Morgan, M J; ,
Abstract: The autodiametric method is a highly streamlined method for estimating fecundity of fish with determinate oocyte development pattern. Greenland halibut presents a peculiar reproductive strategy with two simultaneously cohorts one of large vitellogenic oocytes (for the current year) and another one of small vitellogenic oocytes (for the subsequent year). Results of this study showed that autodiametric method can be applied to estimate fecundity in Greenland halibut. Additionally, spatial differences in the autodiametric calibration curve were observed in the Northwest Atlantic, but did not translate into differences in fecundity at length. This is the first time that spatial differences between ACCs of the same species have been reported, what could be the result of (i) the unusual oocyte development pattern, or (ii) spatial differences in oocyte biochemistry. More research on the relative dynamics of oocyte cohorts simultaneously present in Greenland halibut ovaries and the factors (endo- or exogenous) influencing oocyte packing density could provide a better understanding of observed geographical differences.